A theoretical support for cultural influence implementation and acceptance of assessment centres for Malaysia public sector - Mohd Hanafiah, Ahmad; Mohd Rashid, Ab Hamid (Kolej Yayasan Pahang (KYP), 2018)
This paper aims to provide a theoretical support on how culture influence the implementation and acceptance of assessment centres (ACs) in Malaysia. ACs are a popular technique that has been used and studied for at least 50 years, primarily in Western countries to facilitate HR decisions. The proliferation of ACs around the world has raised questions about their application in specific countries which there is a lack of research into its effectiveness in developing countries. Although studies have found that differences in cultural settings may have an impact on HR practices, very little attention has been given to ACs. Recent studies show ACs approach has also been used in developing countries. Therefore, understanding how culture may influence the implementation of ACs and how this might differ from more developed nations is important. This paper aims to contribute to this research gap by exploring the implementation and acceptance of ACs in Malaysia, as an example of an Eastern, and developing, country. In this context, to analyse how culture influence the design and implementation of ACs, the model of cultural fit is reviewed to explain how culture influences human resource practices and ACs practice. Findings from the literature review show that model of cultural fit can be used to explain how physical and socio-political may influence internal and organisational work culture and, therefore, human resource practices. On the other hand, to understand the influence of culture on acceptance of ACs, organisational justice theory and employee engagement theory are reviewed and used to explain how candidates react to selection process. Findings from literatures search shows that culture may have influence on how ACs participant perceived fairness of the process by which outcomes are reached, or decisions are made.